2017
DOI: 10.1002/cbf.3269
|View full text |Cite
|
Sign up to set email alerts
|

SET domain‐containing protein 5 is required for expression of primordial germ cell specification‐associated genes in murine embryonic stem cells

Abstract: Primordial germ cell (PGC) specification is one of the most fundamental processes in developmental biology. Because PGCs are a common source of both gametes, generation of PGCs from embryonic stem cells (ESCs) is a useful model for analysing the germ line lineage. Although several studies focused on the role of epigenetic regulation on PGC differentiation from ESCs in vitro have been published, germ line commitment remains poorly understood. Here, we show that SET domain-containing protein (Setd5), which has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…However, it has been proposed that SETD5 regulates chromatin accessibility at promoter regions by stimulating histone deacetylase (HDAC) activity, as described for its putative orthologs Set3p and UpSET (Deliu et al, 2018;Osipovich et al, 2016;Rincó n-Arano et al, 2012). Homozygous deletion of Setd5 in mice is lethal at an early embryonic stage due to cardiovascular defects (Osipovich et al, 2016), while its downregulation in embryonic stem cells (ESCs) leads to alterations in myogenic, vasculogenic, and primordial germ cell lineage differentiation (Osipovich et al, 2016;Yu et al, 2017). Few studies are reported on SETD5 molecular function during neural development and maturation and how its inactivation may lead to ID/ASD.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been proposed that SETD5 regulates chromatin accessibility at promoter regions by stimulating histone deacetylase (HDAC) activity, as described for its putative orthologs Set3p and UpSET (Deliu et al, 2018;Osipovich et al, 2016;Rincó n-Arano et al, 2012). Homozygous deletion of Setd5 in mice is lethal at an early embryonic stage due to cardiovascular defects (Osipovich et al, 2016), while its downregulation in embryonic stem cells (ESCs) leads to alterations in myogenic, vasculogenic, and primordial germ cell lineage differentiation (Osipovich et al, 2016;Yu et al, 2017). Few studies are reported on SETD5 molecular function during neural development and maturation and how its inactivation may lead to ID/ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Current findings on SETD5 activity postulates that by interacting with the polymerase‐associated factor 1 complex (PAF1C) and the nuclear receptor co‐repressor (N‐CoR), SETD5 may be involved in chromatin accessibility during transcription (Kim et al, ; Rincon‐Arano et al, ; Osipovich et al, ; Yu et al, ).…”
Section: Molecular Interactions Of Setd5mentioning
confidence: 99%
“…Methyltransferase activity has also not been detected for the SETD5 paralog MLL5 ( Madan et al, 2009 ; Mas-y-Mas et al, 2016 ) or for SETD5 orthologs including yeast Set3p ( Pijnappel et al, 2001 ) and Drosophila UpSET ( Rincon-Arano et al, 2012 ), suggesting that, if SETD5 indeed possesses such catalytic activity, it was acquired during the process of evolution. Proteomics analyses by several research groups have consistently identified components of two complexes—the HDAC3 and PAF1 complexes—among proteins found to associate with SETD5 ( Osipovich et al, 2016 ; Yu et al, 2017 ; Deliu et al, 2018 ; Nakagawa et al, 2020 ; Wang et al, 2020 ; Matsumura et al, 2021 ). The HDAC3 complex functions mainly as a transcriptional repressor by catalyzing deacetylation of histone proteins ( Seto and Yoshida, 2014 ), whereas the PAF1 complex regulates transcription by modulating promoter-proximal pausing, transcriptional elongation and termination, and RNA 3′-end formation by RNA polymerase II ( Branden Van Oss et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%